2012
DOI: 10.1002/ptr.4801
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Activities of Hypericum origanifolium Extract via GABAergic and Opioidergic Mechanisms

Abstract: Pharmacological effects of hydroalcoholic extract prepared from Hypericum origanifolium Willd. (Guttiferae) on behavioral parameters and pain perceptions of mice were investigated in this study. Depression, anxiety, spontaneous locomotor activity, and motor coordination parameters of mice were assessed by modified forced swimming, hole board, activity cage, and rota-rod tests, respectively. In addition, antinociceptive effect was evaluated by performing hot-plate, tail-clip, and formalin tests. Reboxetine (20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Our findings are in accordance with reports on chlorogenic acid and rutin as the main components of extracts widely recognized as antidepressants such as Hypericum extracts [1921]. Moreover, in the case of Hypericum origanifolium , these two components are also the main compounds found in the crude extract, even over hypericin and hyperforin, the compounds described by far as the responsible for the antidepressant properties of Hypericum perforatum (St. John's wort) [22]. …”
Section: Resultssupporting
confidence: 92%
“…Our findings are in accordance with reports on chlorogenic acid and rutin as the main components of extracts widely recognized as antidepressants such as Hypericum extracts [1921]. Moreover, in the case of Hypericum origanifolium , these two components are also the main compounds found in the crude extract, even over hypericin and hyperforin, the compounds described by far as the responsible for the antidepressant properties of Hypericum perforatum (St. John's wort) [22]. …”
Section: Resultssupporting
confidence: 92%
“…The reduction in the number of rearings and crossings may suggest that S. guaraniticum caused alterations in the activity of the central nervous system (Morais, Barbosa-Filho, Almeida, 1998;Mora et al, 2005;Yasar et al, 2012). Further, it is interesting to note that the behavioral effects were more pronounced 48 h after treatment, and the behavior of the rats was similar to the controls at day 14 after treatment.…”
Section: Discussionmentioning
confidence: 91%
“…In this regard, it is important to point out that Fernandez et al . demonstrated that rutin interacted with GABA A receptors in behavioural studies [32–35]. Therefore GABAergic modulation could be a promising target of rutin for alleviating pain.…”
Section: Discussionmentioning
confidence: 97%